ON THE GEOMETRICAL ARRANGEMENT OF THE PROTEIN SUBUNITS OF HUMAN SERUM LOW-DENSITY LIPOPROTEIN: EVIDENCE FOR A DODECAHEDRAL MODEL - Pollard, H. (1969)
Ultracentrifugal and electron microscopic studies of human serum low-density lipoprotein (LDL) and several of its derivatives led to the formulation of a model in which the 20 protein subunits, probably globular, are arranged in a dodecahedral pattern with icosahedral symmetry. In such a model the LDL surface is occupied by both protein and lipids, predominantly phospholipids, as supported by the results of the hydrolysis of LDL by phospholipase A and C. Neutral lipids (cholesterol esters and glycerides) would be in the interior of the molecule.